Disease burden of community acquired pneumonia among children under 5 y old in China: A population based survey - Yan Li; Zhijie An; Dapeng Yin; Yanmin Liu; Zhuoying Huang; Yujie Ma; Hui Li; Qi Li; Huaqing Wang (Taylor & Francis Group, 2017)
Background: To obtain the baseline data on the incidence and cost of community acquired pneumonia among under-5 children for future studies, and provide evidence for shaping China's strategies regarding pneumococcal conjugate vaccine (PCV). Methods: Three townships from Heilongjiang, Hebei and Gansu Province and one community in Shanghai were selected as study areas. A questionnaire survey was conducted to collect data on incidence and cost of pneumonia among children under 5 y old in 2012. Results: The overall incidence of clinically diagnosed pneumonia in children under 5 y old was 2.55%. The incidence in urban area was 7.97%, higher than that in rural areas (1.68%). However, no difference was found in the incidences of chest X-ray confirmed pneumonia between urban and rural areas (1.67% vs 1.23%). X-ray confirmed cases in rural and urban areas respectively accounted for 73.45% and 20.93% of all clinically diagnosed pneumonia. The hospitalization rate of all cases was 1.40%. Incidence and hospitalization rate of pneumonia decreased with age, with the highest rates found among children younger than one year and the lowest among children aged 4 (incidence: 4.25% vs 0.83%; hospitalization: 2.75% vs 0.36%). The incidence was slightly higher among boys (2.92% vs 2.08%). The total cost due to pneumonia for the participants was 1138 733 CNY. The average cost and median cost was 5722 CNY and 3540 CNY separately. Multivariate analysis showed that the only factor related to higher cost was hospitalization. Conclusions: The disease burden was high for children under 5 y old, especially the infant. PCV has not been widely used among children, and thus further health economics evaluation on introducing PCV into National Immunization Program should be conducted.